2009
DOI: 10.1124/jpet.109.152009
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Orexin-1 Receptors Attenuates Orexin-2 Receptor Antagonism-Induced Sleep Promotion in the Rat

Abstract: Orexins are peptides produced by lateral hypothalamic neurons that exert a prominent role in the maintenance of wakefulness by activating orexin-1 (OX1R) and orexin-2 (OX2R) receptor located in wake-active structures. Pharmacological blockade of both receptors by the dual OX1/2R antagonist (2R)-2-[(1S)-6,7-dimethoxy-1-{2-[4-(trifluoromethyl)phenyl]ethyl}-3,4-dihydroisoquinolin-2(1H)-yl]-N-methyl-2-phenylethanamide (almorexant) has been shown to promote sleep in animals and humans during their active period. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
237
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(261 citation statements)
references
References 35 publications
21
237
3
Order By: Relevance
“…Finally, the compounds were tested at the defined doses in the BE model. OX 1 R and OX 2 R antagonists are reported in the literature to be involved in the control of sleep, in particular to induce hypnotic effects (Di Fabio et al, 2011;Gozzi et al, 2011;Dugovic et al, 2009). In a preclinical hypnotic sleep model in male rats, the results obtained demonstrated that the dual OX 1 /OX 2 R antagonist, SB-649868, induced a robust hypnotic effect, both on the ability to induce and to maintain sleep, reaching a statistically significant effect at 3 mg/kg.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Finally, the compounds were tested at the defined doses in the BE model. OX 1 R and OX 2 R antagonists are reported in the literature to be involved in the control of sleep, in particular to induce hypnotic effects (Di Fabio et al, 2011;Gozzi et al, 2011;Dugovic et al, 2009). In a preclinical hypnotic sleep model in male rats, the results obtained demonstrated that the dual OX 1 /OX 2 R antagonist, SB-649868, induced a robust hypnotic effect, both on the ability to induce and to maintain sleep, reaching a statistically significant effect at 3 mg/kg.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the simultaneous antagonism of both OX 1 R and OX 2 R or the selective inhibition of OX 2 R results in the induction of a strong hypnotic effect (Brisbare-Roch et al, 2007;Dugovic et al, 2009;Di Fabio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BzRAs are effective for the induction of sleep, they can have detrimental effects on cognitive performance (Huang et al, 2010;Uslaner et al, 2013;Wesensten et al, 1996), resulting in the need for hypnotics with an improved cognitive profile. Because of the involvement of the Hcrt system in sleep and arousal, Hcrt receptor (HcrtR) antagonists have been extensively investigated for the treatment of insomnia (Brisbare-Roch et al, 2007;Dugovic et al, 2009;Morairty et al, 2014;Roecker and Coleman, 2008;Uslaner et al, 2013;Winrow et al, 2011) and are thought to promote sleep through selective disfacilitation of wake-promoting systems.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, almorexant was well tolerated with no signs of cataplexy, suggesting that acute, short-lived, intermittent temporary blockade of orexin receptors will not result in a narcolepsy-like phenotype(40). Recently, repeated administration of an OXR-2 selective antagonist, JNJ-10397049, was shown to decrease the latency for persistent sleep and increased NREM sleep time more potently than did the dual antagonist, almorexant (41), while, an OXR-1 selective antagonist SB-408124 had no effect on sleep parameters. Rather, the OXR-1 antagonist attenuated the sleep-promoting effects of the OXR-2 antagonist when simultaneously administered, possibly by increasing dopamine release in the prefrontal cortex.…”
Section: Therapeutic Potential Of Drugs That Target the Orexin Receptorsmentioning
confidence: 99%